The development of Taiwanese folk religion, 1683-1945 - Chen, Hsinchih (My University, 1995)
The development of Taiwanese folk religion was intertwined with social and economic conditions through Taiwan's history. Since the 17th century, the new immigrant society favored the growth of economic crops to exchange the necessary goods from mainland. This started the long process of dynamic interaction between the folk religion and the economic development of Taiwan. As a result, the original roles of the deities, Ma-tsu (a protector of seamen) and T'u-ti-kung (a protector of farmers) had changed and gradually emerged as commercial gods. The official culture did not root deeply in this new society, so the official temples without the local support, were doomed to decline.Under the Japanese rule, the Taiwanese were barred from government positions but active in economic field. Hence, the content of folk religion, articulating their life, became more concerned with material gains. Without the involvement of high-culture elites in shaping the beliefs, moral or abstract values were less emphasized in the religion. Although the religion is an important part of the cultural identity of the Taiwanese, there was no dramatic and violent confrontation between the folk religion and colonial rule. Only a few Taiwanese converted to the religions that the rulers promoted, although the folk religion adopted some new elements from the Japanese religions.Another important aspect of this study is that the study of Taiwanese folk religion can offer an alternative view to the Western general theory of religious study, which assumes that state and religion are independent institutions, and is unworkable for some religions such as Taiwanese folk religion. Data for the temples of this study mainly come from three sources: (1) Ch'ing Gazetteers (written from 1694 to 1898), (2) The Survey of Temples (six volumes) (conducted by the colonial government in 1915-1916), (3) Appendix: Directory of Temples in Taiwan, in Taiwanese Religion and Superstitious Customs (So, Keirai, 1938).
Thesis (Ph. D.)--University of Washington, 1995
Keywords: Theses--Sociology